Підвищення завадостійкості кабелів для систем протипожежного захисту - Безпрозванних, Ганна Вікторівна; Пушкар, Олег Анатолійович (Національний технічний університет "Харківський політехнічний інститут", 2020)
Наведено частотні залежності перехідного загасання на ближньому кінці в 10, 30 та 4-х парних симетричних кабелях. Експериментально доведено, що скручування кожної пари з різними кроками забезпечує більш високий рівень завадостійкості кабелів на основі витих пар. Застосування загального екрану призводить до зменшення електромагнітних впливів між витими парами кабелю. Діапазон значень перехідного затухання на ближньому кінці на верхній робочій частоті 100 МГц становить 44 – 54 дБ та 46 – 58 дБ для неекранованого та екранованого кабелів з витими парами відповідно. Ефект зростання коефіцієнту загасання та більший розкид параметрів впливу обумовлює більш жорсткі вимоги до щільності конструкції та налаштувань технологічного процесу виготовлення екранованих кабелів.

Technical means of fire protection systems are capable of operating at data rates from tens to hundreds of Kbit/s with components of a digital signal in the frequency spectrum up to several tens of MHz. Appropriate cable infrastructure with a high level of noise immunity is required to transmit broadband digital signals. Purpose. Substantiation of ways to increase noise immunity of cables based on twisted pairs for modern fire protection systems with the ability to transmit digital signals in the frequency spectrum up to 100 MHz. Methodology. A comparison is made of the influence of the twisting step of pairs in unshielded 4-pair and multi-pair shielded balanced cables on the parameters of electromagnetic effects. It has been experimentally shown that twisting each pair with different steps provides a higher level of noise immunity of cables based on twisted pairs. Practical value. The frequency dependencies of the near end crosstalk in 10-, 30- and 4-pair balanced cables are shown. The influence of the common shield on the attenuation coefficient of the shielded 4-pair cable is established.
Increasing noise immunity of cables for fire protection systems
Keywords: кручені пари; неекранований і екранований кабелі; коефіцієнт загасання; twisted pairs; unshielded and shielded cables; attenuation coefficient